TEACHER’S CHALLENGES IN USING GAME-BASED-LEARNING MEDIA FOR YOUNG LEARNERS AT SD RK II FRANSISKUS PADANG - Sari, Nadea Kirana; Rani, Yati Aisya (Universitas Negeri Padang, 2025)
The primary objective of this study is to analyze the challenges faced by English teachers in implementing Game-Based Learning (GBL) for young learners at SD RK II Fransiskus Padang. This research employs a qualitative descriptive design, with data collected through interviews. The methodology focuses on identifying technological, pedagogical, and content-related challenges in GBL implementation.The findings reveal that technological challenges include limited student access to mobile devices and the absence of interactive monitors, hindering direct engagement. Pedagogically, while GBL enhances motivation and participation, it also creates classroom management difficulties, leading to teacher exhaustion. To address disengaged students, teachers use adaptive grouping strategies. In contrast, no major content-related challenges were found, as teachers can easily access suitable learning materials online.In conclusion, despite technological and pedagogical challenges, GBL remains an effective method for improving student engagement in English learning. Schools should invest in better technological resources, and teachers need to refine classroom management strategies to maximize GBL’s benefits. Future research could explore strategies to further enhance GBL implementation and its long-term impact on student learning outcomes.